Residential segregation and educational performance. The case of Athens. (November 2019) - Maloutas, Thomas; Spyrellis, Stavros Nikiforos; Capella, Antoinetta
This paper investigates the relationship among length of educational training, social origin and residential segregation in Athens using a large sample of 130, 000 young individuals 15 to 27 years old, as recorded in the 2011 census. Hypotheses based on high binary correlations between the length of training and a number of variables indicating social origin and the social status of residential areas were tested with a generalised linear mixed model to determine the significance of the influence of these variables on the length of educational training. A separate analysis was conducted for each age group, roughly corresponding to education levels – upper secondary (15–18 years old), undergraduate (19–22 years) and postgraduate (23–27 years). It was assumed that at each level the range and the shape of the socially and spatially unequal access to education would be significantly different. A scenario regarding the city's important vertical segregation was also explored. It was assumed that living on different floors in the vertically segregated apartment buildings of the city's densely built central neighbourhoods might be significantly related to the length of educational training, even after controlling for social class/status.